2019
DOI: 10.3390/antiox8060170
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Tea for the Prevention and Management of Diabetes Mellitus and Diabetic Complications: An Updated Review

Abstract: Diabetes mellitus has become a serious and growing public health concern. It has high morbidity and mortality because of its complications, such as diabetic nephropathy, diabetic cardiovascular complication, diabetic neuropathy, diabetic retinopathy, and diabetic hepatopathy. Epidemiological studies revealed that the consumption of tea was inversely associated with the risk of diabetes mellitus and its complications. Experimental studies demonstrated that tea had protective effects against diabetes mellitus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 154 publications
(158 reference statements)
0
77
0
3
Order By: Relevance
“…Previous studies have revealed that the consumption of tea is inversely associated with the risk of diabetes mellitus and its complications. Experimental studies have shown that tea has protective effects against diabetes by enhancing insulin action, ameliorating insulin resistance, scavenging free radicals, and decreasing inflammation 30 . Our results indicated that people who were obese (BMI) and had an unfavourable dietary quality had a high risk of prediabetes, and abdominal obesity and obesity (BMI) are significantly associated with an increased risk of diabetes, as they can cause abnormal glucose metabolism 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the consumption of tea is inversely associated with the risk of diabetes mellitus and its complications. Experimental studies have shown that tea has protective effects against diabetes by enhancing insulin action, ameliorating insulin resistance, scavenging free radicals, and decreasing inflammation 30 . Our results indicated that people who were obese (BMI) and had an unfavourable dietary quality had a high risk of prediabetes, and abdominal obesity and obesity (BMI) are significantly associated with an increased risk of diabetes, as they can cause abnormal glucose metabolism 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had confirmed the toxic effects of aflatoxicosis in the different body systems through its direct effect in liberating the reactive oxygen species (ROS) causing cellular damages (Josse, Dumont, Fautre, Robin, & Guillouzo, 2012). Black tea (BTE) was known for its antioxidant effects (Kumar & Rizvi, 2014), it mitigates the aflatoxicosis via several evidences, that is, normalizing the concentrations of total proteins, AST, and ALT (Jha et al., 2013), and lowering the hypercholesterolemia (Troup et al, 2015) and nephropathy (Meng et al., 2019). Likewise, Suryanarayana, Satyanarayana, Balakrishna, Kumar, and Reddy (2007) and Tokaç et al.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a protective effect of EGCG on pancreatic cell function. Meng et al showed that EGCG can inhibit inflammation by reducing reactive oxygen species and downregulating the production of inducible nitric oxide synthetase (iNOS) [56]. Furthermore, EGCG increases glucose tolerance [57] and decrease HbA1c levels in STZ-induced diabetes in rats, contributing to further prevention of diabetic complications [58].…”
Section: Protective Effects Of Egcg On Pancreatic and Hepatic Cell Fumentioning
confidence: 99%